Water-in-acid gel polymer electrolyte realized through a phosphoric acid-enriched polyelectrolyte matrix toward solid-state supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Torris, Arun A. T.; Chandran, Nikhil M. K.; Nair, Sanoop B.; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Sustainable Chemistry & Engineering, 2018)
A new concept of water-in-acid gel polymer electrolytes (GPEs) is introduced. The simple and scalable UV-light-assisted synthesis of a copolymer matrix possessing polyelectrolyte behavior, followed by swelling in minimally diluted H3PO4 (15.1 M/88 wt % aqueous solution), effects formation of a high proton-conducting, self-standing, and mechanically stable polyelectrolyte GPE (PGPE). Retention of high mechanical stability despite the presence of a large amount of liquid species makes it a promising candidate for replacing conventional GPEs. The high proton conductivity (9.8 X 10(-2) S cm(-1)) of the PGPE at an ambient temperature of 303 K is attributed to the high concentration of the conducting species present in the polymer matrix. The PGPE-based polyaniline (PANI) supercapacitor device (PANI-1) with a mass loading of 1 mg cm(-2) exhibits a high specific gravimetric capacitance of 385 F g(-1) at a current density of 0.25 mA cm(-2). At the same current density, the PANI-5 device retains high gravimetric and areal capacitance values of 258 F g(-1) and 1288 mF cm(-2), respectively. The low equivalent series resistance value of 0.78 Omega (for the PANI-5 device) further proves the excellent electrode-electrolyte interface formed by the water-in-acid GPE. A 100% capacitance retention even after 9000 continuous charge-discharge cycles strongly indicates the feasibility of adopting water-in-acid GPEs in future supercapacitors.